EFFECT OF COMBINING PHALERIA MACROCARPA AND AVERRHOA BILIMBI L ON FASTING BLOOD GLUCOSE LEVES IN A RAT MODEL OF TYPE 2 DIABETES MELLITUS - Fathurrahman Fathurrahman; Widyastuti Hartati, Niken; Aprianti Aprianti; Laila Sholehah (The Indonesian Journal of Public Health, 2025)
Introduction: Diabetes is a serious problem, and a solution is being sought. Traditional ingredients have been proven to contain many substances that can be used to prevent and treat diabetes. This study aimed to investigate the effects of a combination of Phaleria macrocarpa and Averrhoa bilimbi L extracts on fasting blood glucose levels. Methods: A randomized, post-test-controlled group design was used. Type 2 diabetes mellitus was induced in 36 Sprague Dawley rats by feeding them a high-fat diet for 2 weeks, followed by the administration of streptozotocin and nicotinamide to induce type 2 Diabetes Mellitus. The rats were divided into six groups: CN, C-, C+, T1, T2, and T3. The treatment was administered for 21 days, and fasting blood glucose levels were measured. The data were analyzed using One-Way ANOVA with post-hoc Tukey's HSD test. Results: The combined dose of Phaleria macrocarpa and Averrhoa bilimbi Lextract effectively reduced fasting blood glucose levels over a 21-day period. Group T1 demonstrated the highest efficacy and did not differ significantly from that of the C+ group. The effective dosage that influenced fasting blood glucose levels was a combination of Phaleria macroca at 750 mg/kg W/day and Averrhoa bilimbi L at 375 mg/kg. Conclusion: Phaleria macrocarpa and Averrhoa bilimbi L extract have a synergistic effect that makes them a promising natural medication for controlling blood glucose levels. Further investigation is required to investigate the underlying mechanisms and assess the long-term consequences of this combination therapy.